An analysis of the Jamaican business cycle - Whyte, Sushana ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2008)
Defines the Jamaican business cycle and estimates coincident and leading indexes. Provides a channel for improving the Bank's forecast of economic growth.